Faktor-faktor yang Mempengaruhi Penghentian Prematur Prosedur Audit - Supardi, Deddy (Jurnal Trikonomika, 2011)
Premature sign-off and under reporting audit time are two of the negative behaviours that may result from time budget pressures. The objectives of this research are: first, is internal auditor to do premature sign-off and second testing the significant influence of audit program, time budget pressure, evaluation of performance internal auditor, review and supervision, and professional judgement on premature sign-off audit procedures. The sample used were the internal auditor working in various of companies. Sample were randomly selected using questionaires are many as 93. Logistic regression is used in investigating the hypotheses. The results of this research show that premature sign-off influence by time budget pressure, evaluation of performancer and professional judgement.